Differences in the survival rates of older patients with colorectal cancers in 2003 and 2009 - Shin, Je-Wook (Ann Surg Treat Res, 2017)
PURPOSE: The aim of this study was to investigate survival in patients aged ≥70 years who underwent colorectal cancer surgery in 2003 and 2009. In addition, we aimed to identify the factors that could affect survival in these patients. METHODS: In a cross-sectional study, a retrospective review of the data for 878 patients who underwent colorectal cancer surgery with curative intent in the years 2003 and 2009 was performed. The primary outcome was the 5-year overall survival rate (5-OSR), and the clinicopathologic factors that could affect overall survival were analyzed. RESULTS: The 5-OSR was 77.8% and 84.9% in 2003 and 2009, respectively (P = 0.013). Age, American Society of Anesthesiologists physical status classification, stage, type of surgery, and length of hospital stay possibly affected survival per the univariate and multivariate analyses. In patients aged ≥70 years, the 5-OSR in 2009 was 75.9%, which showed improvement compared to 53.7% in 2003 (P = 0.027). The stage, type of surgery, and hospital stay were the variables that possibly affected survival in patients aged ≥70 years per the univariate analysis, whereas the stage (III; hazard ratio [HR], 2.188; P = 0.005) and length of hospital stay (>12 days; HR, 2.307; P = 0.004), were the variables that showed statistical significance on the multivariate analysis. CONCLUSION: We found that early stage and shortening the length of hospital stay could affect survival in older patients with colorectal cancers. Because of limited evidence on the influence of shortening the length of hospital stay on survival in older patients, further investigations are warranted.